Determinant Factors of Sustainability Business Performance: The Role of Innovation Capability - Setiyowati, Wulan; Pratama, Bima Cinintya; Wahyuni, Sri; Pramurindra, Rezky (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2025)
This study aims to examine the influence of determinants of sustainability business performance in the form of intellectual capital, financial technology, and entrepreneurial capability and explore the role of innovation capability as a mediator. This study used a questionnaire to collect data on MSMEs in Banyumas Regency, Central Java, and 198 respondents were analyzed using the Smart-PLS approach. The results showed a positive influence between intellectual capital, financial technology, and entrepreneurial capability on sustainability business performance and a positive influence of innovation capability as a mediator. The findings of this study provide contributions for MSME actors. First, maximizing resource utilization is key to improving performance and influencing business sustainability. Second, collaboration between internal factors and technology utilization is vital in creating sustainable business for MSMEs. Third, this study explains the driving factors companies can use to develop their internal potential to create a sustainable business.